Strategies used by French Alpine guides to adapt to the effects of climate change. (March 2020) - Mourey, Jacques; Perrin-Malterre, Clémence; Ravanel, Ludovic
Abstract: The effects of climate change on high mountain environments are seriously affecting summer Alpine climbing. Summer mountaineering in the Alps has become progressively more dangerous and technically difficult in recent years and good periods for mountaineering tend to be unpredictable in summer and have shifted towards spring, autumn and even winter for some routes. In this context, this research paper ̶ based on a questionnaire survey and semi-structured interviews ̶ examines how French Alpine guides are affected by climate change and how they adapt accordingly. This study enabled us to identify 33 methods of adaptation which we grouped in 5 main strategies. Two categories of Alpine guides were distinguished. One seems to have difficulties in adapting to the effects of climate change while the other seems to face the challenge with greater ease. This difference depends on the activities which each Alpine guide chooses to practice. In summer, those guides who mainly practice traditional mountaineering are less adaptable than those who have diversified, offering activities which can be done outside the high mountain environment. Alpine guides have the possibility to adapt through the diversification of their activities. However, this implies a redefinition of their job that does not always correspond to their preferred vision of the profession.